2018
DOI: 10.4067/s0719-81322018000100104
|View full text |Cite
|
Sign up to set email alerts
|

Energetic metabolic profile of ewes presenting low body condition score induced to subclinical hypocalcemia in early postpartum

Abstract: ABSTRACT. The aim of the present study is to assess plasma concentrations of metabolites related to energy balance in ewes showing low body condition score (BCS) induced to subclinical hypocalcemia in early postpartum. Sixteen crossbred ewes (Ideal x Corriedale) presenting BCS <3 were divided in two groups: 1) control group (n = 9), which received no treatment, and 2) hypocalcemia group (n = 7), which was subjected to twelve hours of induced subclinical hypocalcemia through intravenous Na 2 EDTA infusion six h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Glucose levels decrease throughout pregnancy (77.10±1.03, 70.32±0.55, 66.03±3.07mg/dL), meeting the energy demands of fetal development and lactation, and return to early pregnancy levels in the postpartum stage (86.78±0.12mg/dL). The rise in postpartum blood glucose levels could also be attributed to the increased cortisol release observed following lambing in meat crossbred ewes (Schmitt et al 2018). Nonetheless, it is noteworthy that glucose levels in all the animals within our study fell within the physiological range for sheep, as reported in previous studies (Pesántez-Pacheco et al 2019, Iqbal et al 2022.…”
Section: Serum Leptin Vitamin D Glucose and Triglyceridessupporting
confidence: 81%
“…Glucose levels decrease throughout pregnancy (77.10±1.03, 70.32±0.55, 66.03±3.07mg/dL), meeting the energy demands of fetal development and lactation, and return to early pregnancy levels in the postpartum stage (86.78±0.12mg/dL). The rise in postpartum blood glucose levels could also be attributed to the increased cortisol release observed following lambing in meat crossbred ewes (Schmitt et al 2018). Nonetheless, it is noteworthy that glucose levels in all the animals within our study fell within the physiological range for sheep, as reported in previous studies (Pesántez-Pacheco et al 2019, Iqbal et al 2022.…”
Section: Serum Leptin Vitamin D Glucose and Triglyceridessupporting
confidence: 81%
“…This greater availability of glucose may reflect an adaptation to the presence of multiple fetuses in the high-producing Lacaune dairy breed [41]. It may also result from the greater release of cortisol after multiple lambings previously observed in meat crossbred ewes [42]. Studies in Würtenberg breeds have also reported higher levels of plasma glucose in milk-producing ewes than in non-lactating, pregnant ewes [43].…”
Section: Discussionmentioning
confidence: 99%
“…During the 30 days of the study, the Lacaune sheep did not clinically present any disease, so this increase in the mean protein values in both groups could be related to the total protein supply in the diet, which was 22% per day throughout the trial period. This value of crude protein offered to the sheep in the peripartum period was higher than that offered in other studies (PICCIONE et al, 2009;SCHMITT et al, 2018), and according to Rankins (2005), sheep in the lactation period need a diet with about 13.5% crude protein.…”
Section: Resultsmentioning
confidence: 61%